Analisis Respon Mahasiswa Terhadap Pembelajaran Menggunakan Media Youtube Pada Mata Kuliah Bahasa Indonesia - Sofiyulloh (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
The digital era, as we are currently experiencing, has made all lines of life visible in the digital world. Most people can definitely access YouTube. Until now, YouTube has become the social media network that is most in demand by adults and even children. Can not be separated in the world of education itself, teaching staff can really take advantage of this media to support teaching and learning activities. The formulation of the problem in this study is how students respond to learning using YouTube Media as a teaching medium in Indonesia language, analyzing how students' interest and motivation in learning introductory education courses. This research uses descriptive qualitative method. The research subjects were 32 students in semester 1 of the Islamic religious education study program in the odd semester of the 2023/2024 cademic year. This study aims to describe the perceptions of Unsulbar students towards YouTube media and the effects that arise after accessing learning materials through YouTube media. As many as 90.3% of 32 students stated that they liked YouTube media to be used as a learning medium and this research can provide an empirical basis for the benefits of YouTube developed by lecturers as a learning medium in introductory lectures and other courses in tertiary institutions